Hydrothermal sulfide accumulation along the Endeavour Segment, Juan de Fuca Ridge - Jamieson, J W; Clague, D A; Hannington, M D (Earth and Planetary Science Letters, 2014)
Hydrothermal sulfide deposits that form on the seafloor are often located by the detection of hydrothermal plumes in the water column, followed by exploration with deep-towed cameras, side-scan sonar imaging, and finally by visual surveys using remotely-operated vehicle or occupied submersible. Hydrothermal plume detection, however, is ineffective for finding hydrothermally-inactive sulfide deposits, which may represent a significant amount of the total sulfide accumulation on the seafloor, even in hydrothermally active settings. Here, we present results from recent high-resolution, autonomous underwater vehicle-based mapping of the hydrothermally-active Endeavour Segment of the Juan de Fuca Ridge, in the Northeast Pacific Ocean. Analysis of the ridge bathymetry resulted in the location of 581 individual sulfide deposits along 24 km of ridge length. Hydrothermal deposits were distinguished from volcanic and tectonic features based on the characteristics of their surface morphology, such as shape and slope angles. Volume calculations for each deposit results in a total volume of 372,500 m3 of hydrothermal sulfide–sulfate–silica material, for an equivalent mass of ∼1.2 Mt of hydrothermal material on the seafloor within the ridge's axial valley, assuming a density of 3.1 g/cm3. Much of this total volume is from previously undocumented inactive deposits outside the main active vent fields. Based on minimum ages of sulfide deposition, the deposits accumulated at a maximum rate of ∼400 t/yr, with a depositional efficiency (proportion of hydrothermal material that accumulates on the seafloor to the total amount hydrothermally mobilized and transported to the seafloor) of ∼5{%}. The calculated sulfide tonnage represents a four-fold increase over previous sulfide estimates for the Endeavour Segment that were based largely on accumulations from within the active fields. These results suggest that recent global seafloor sulfide resource estimates, which were based mostly on the sizes and distribution of hydrothermally-active deposits, may be similarly underestimating the amount of sulfide along the global submarine neovolcanic zones.
Keywords: AUV ABE (Autonomous Benthic Explorer); HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)